ON POETIC CONTINUITIES AND DISCONTINUITIES: (Novel Klobuk by Petar Sarić in the context of his novelistic poetics) (Heritage, 2022)
Interpretation of an author's literary work compared to other literary works of the same author necessarily leads to understanding the similarities and differences that this work brings in relation to those that precede it, which means that it is necessary to talk about poetic continuities (which are inevitable) and poetic discontinuities (which are expected). Deciding to connect the plot of his latest novel Klobuk (2021) to the drama of a hero - Turkish leader Asan Begenišić, who was taken to the Janissaries as a child - Šaric made a step into the more distant past than he does in his earlier novels, but remained consistently faithful to the recognizable epic environment, patriarchal culture and tradition, way of storytelling, etc., With his focus on events and character(s) from the historical past and the Montenegrin space, with his novel Klobuk Petar Sarić expresses his consistency with his poetic world, well known from the novels Dečak iz Lastve, Petruša i Miluša, Sutra stiže Gospodar, Strah od svetlosti and Sara. However, he connected the basic story of the novel - the story of klobuk dizdar Asan (Jovan) Begenišić  - with the memory of the story he grew up with, which significantly influenced the formation of the world of his literary work. The focus on the personal drama of the protagonist makes this novel by Sarić more psychologically complex, and the emphasized process of symbolization and open concept of narration more modern in relation to everything that this writer published during half a century of creation.  With his latest novel, Sarić showed not only full creative and narrative maturity, but also the ability and courage to bring the elements that make up probably his greatest quality into the built and recognizable poetic world of his novels. This primarily refers to the symbolic layer of the novel with which the writer made the greatest poetic discontinuity in relation to previous achievements.
Keywords: Petar Sarić, Klobuk, novelistic poetics, poetic continuity, poetic discontinuity, motives, language, style, symbolization